How to Validate Data Quality in a Trauma Registry? The Helsinki Trauma Registry Internal Audit. (June 2021) - Heinänen, M.; Brinck, T.; Lefering, R.; Handolin, L.; Söderlund, T.
Background and Aims: Trauma registry data are used for analyzing and improving patient care, comparison of different units, and for research and administrative purposes. Data should therefore be reliable. The aim of this study was to audit the quality of the Helsinki Trauma Registry internally. We describe how to conduct a validation of a regional or national trauma registry and how to report the results in a readily comprehensible form. Materials and Methods: Trauma registry database of Helsinki Trauma Registry from year 2013 was re-evaluated. We assessed data quality in three different parts of the data input process: the process of including patients in the trauma registry (case completeness); the process of calculating Abbreviated Injury Scale (AIS) codes; and entering the patient variables in the trauma registry (data completeness, accuracy, and correctness). We calculated the case completeness results using raw agreement percentage and Cohen's κ value. Percentage and descriptive methods were used for the remaining calculations. Results: In total, 862 patients were evaluated; 853 were rated the same in the audit process resulting in a raw agreement percentage of 99%. Nine cases were missing from the registry, yielding a case completeness of 97.1% for the Helsinki Trauma Registry. For AIS code data, we analyzed 107 patients with severe thorax injury with 941 AIS codes. Completeness of codes was 99.0% (932/941), accuracy was 90.0% (841/932), and correctness was 97.5% (909/932). The data completeness of patient variables was 93.4% (3899/4174). Data completeness was 100% for 16 of 32 categories. Data accuracy was 94.6% (3690/3899) and data correctness was 97.2% (3789/3899). Conclusion: The case completeness, data completeness, data accuracy, and data correctness of the Helsinki Trauma Registry are excellent. We recommend that these should be the variables included in a trauma registry validation process, and that the quality of trauma registry data should be systematically and regularly reviewed and reported.